Gender Semiotics in the Film "The Breadwinner" - Delvie Nellaety (Eduvest - Journal of Universal Studies, 2024)
The Breadwinner film is one of the films that have elements related to gender in it. The approach of this research is a qualitative descriptive research type, with data analysis using the method of Miles and Huberman. The semiotic analysis used the Roland Barthes analysis model which divides the stages into three, namely denotation, connotation, and myth. The results of this study are that gender in this film has a denotative meaning where women have demands to behave and act according to their environment, a connotative meaning where people put a lot of emphasis on how women should behave through verbal utterances, and myths about culture taken from one interpretation of the verses of the Al-Quran regarding women.